Multipositional Colour Picture Tube Test System - Augutis, V.; Gailius, D.; Dumčius, A.; Milinskas, A.; Vaičikonis, E.; Alekna, G. (Elektronika ir Elektrotechnika, 2006)
In this paper the peculiarities of color picture tubes testing system design are considered. The testing system structure and engineering solutions are given. The hardware of modern testing system must be flexible, as it has been indicated by research results. Ill. 6, bibl. 5 (In English; summaries in English, Russian and Lithuanian).